Hormonal Mechanisms of Neuroendocrine Response and Adaptation to Extreme Environmental Factors (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In this paper presented current state about hormonal changes in sympathetic-adrenal, hypophysis-adrenal, hypophysis-gonads and thyroid levels from extreme environment factors. It’s shown that hypophysis gonads and thyroid endocrine links along with sympathetic adrenal, hypophysis adrenal axes are very important relevance in response to extreme environment factors and organism adaptation. In this time a hormonal secretion changes corresponds as interrelated reactions cascade in mechanisms of homeostasis maintenance. A studying of this mechanisms and revealing of its role in stress pathogenesis is fundamental biomedical investigation task. A problem solving allow to perfect prophylactic and treatment methods against stress diseases.